MENENTUKAN SWIMMING LAYER DAN DISTRIBUSI IKAN PELAGIS DI LAUT FLORES BAGIAN BARAT DENGAN DETEKSI AKUSTIK - Donwill Panggabean; Rauzatul Nazzla (Bogor Agricultural University, 2020)
The purpose of this study determined the swimming layer and distribution of pelagic fish in the waters west of the Flores Sea through acoustic detection. Experimental fishing is a method used with two data analyses: 1) analysis of acoustic data at sampling stations with stationery techniques; and 2) analysis of acoustic data along transects between stations. The detection results at stationery 1 showed a very low abundance of pelagic fish, distributed at layer 4 (150-200 m) at night and suspected to be a large pelagic type of tuna with a small amount. The detection results on stationery 2 and stationery 3 are relatively the same, showing a relatively higher abundance compared to stationery 1. Detection results for transects between stations 1-2, 2-3, 3-4, and 4-5 starting from Dewakang waters to east of Takarawataya waters did not detect schooling fish but only single fish. On transects between stations 5-6 very low abundance, the highest mean abundance of 0.5 fish/1000 m3 was detected at layer 4 (150-200 m). On transects between stations 6-7 the abundance was not too high, the highest mean abundance was detected at layer 3 of 10.8 fish/1000 m3. The transect between stations 7-8 is the highest abundance of all transects, the highest abundance average value detected at layer 3 is 20.3 fish/1000 m3. On transects between stations 8-9 the abundance was not too high, schooling tended to be present in all layers, and the highest mean abundance was detected at layer 4 of 1.3 fish/1000 m3. The results of the study concluded that the abundance of pelagic fish in the western Flores Sea is distributed in layers 3 and 4 (100-200 m). Keywords: Acoustic, distribution, pelagic fish, Flores Sea, layer